2020
DOI: 10.1148/radiol.2019191337
|View full text |Cite
|
Sign up to set email alerts
|

Interval and Consecutive Round Breast Cancer after Digital Breast Tomosynthesis and Synthetic 2D Mammography versus Standard 2D Digital Mammography in BreastScreen Norway

Abstract: B reast cancer is the most common type of cancer among women worldwide, with almost 2.1 million new cases in 2018, and early detection with mammographic screening is considered beneficial to reduce mortality from this disease (1,2). Studies using a paired design have demonstrated a higher rate of screen-detected breast cancer when using standard two-dimensional (2D) digital mammography (DM) in combination with digital breast tomosynthesis (DBT) versus DM alone (3,4), and a randomized controlled trial from Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 20 publications
5
48
0
1
Order By: Relevance
“…A few studies evaluating tumor characteristics associated with interval cancer before and after the integration of DBT have largely found similarities between the two groups 3,10,12 . In our study, the vast majority of interval cancers were invasive (DM group: 88.9% invasive, DBT group: 87.5% invasive) rather than in situ in both groups.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…A few studies evaluating tumor characteristics associated with interval cancer before and after the integration of DBT have largely found similarities between the two groups 3,10,12 . In our study, the vast majority of interval cancers were invasive (DM group: 88.9% invasive, DBT group: 87.5% invasive) rather than in situ in both groups.…”
Section: Discussionsupporting
confidence: 50%
“…Several studies investigating differences in interval cancer rates in the current literature found no statistically significant differences in rates of interval cancer rates between the two screening modalities 9,10,12 . While these studies occurred at academic institutions, our study evaluated a large community‐based practice and a greater total number of mammograms (236 845) were included in our study.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations